2020
DOI: 10.1038/s41419-020-02938-4
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species mediate anlotinib-induced apoptosis via activation of endoplasmic reticulum stress in pancreatic cancer

Abstract: Anlotinib (AL3818), a novel multi-targeted receptor tyrosine kinase inhibitor, has recently been proven to be an antitumour drug. This study aimed to explore the antitumour effect of anlotinib and its underlying molecular mechanisms in human pancreatic cancer (PC) cells. The anti-proliferative effect of anlotinib for three PC cell lines was validated using CCK-8, colony formation and EdU detection assays. Cell cycle, cell apoptosis, and reactive oxygen species (ROS) detection assays, a PC xenograft model and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 39 publications
1
37
0
Order By: Relevance
“…Anlotinib inhibits proliferation and induces apoptosis of pancreatic cancer cells, as shown in this work and in a recent study by Yang L. et al (2020) . In addition, our work also revealed that anlotinib impairs the migration and invasion capability of pancreatic cancer cells ( Figures 1E–H ).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Anlotinib inhibits proliferation and induces apoptosis of pancreatic cancer cells, as shown in this work and in a recent study by Yang L. et al (2020) . In addition, our work also revealed that anlotinib impairs the migration and invasion capability of pancreatic cancer cells ( Figures 1E–H ).…”
Section: Discussionsupporting
confidence: 83%
“…This phenomenon is observed in this work, as cell cycle assay showed that the ratio of pancreatic cancer cells in G2/M phase was dramatically elevated after anlotinib treatment ( Figures 2D–G ). Transcriptomics analysis has been applied to explore the mechanism of anlotinib in several tumors like intrahepatic cholangiocarcinoma, pancreatic cancer, colon cancer, and synovial sarcoma ( Tang et al, 2019 ; Song et al, 2020 ; Sun et al, 2020 ; Yang L. et al, 2020 ). Yang L. et al (2020) reported that DEGs in pancreatic cancer cells with anlotinib treatment are associated with apoptosis and ER stress, and demonstrated that anlotinib induces apoptosis of pancreatic cancer cells through the activation of ER stress via PERK/p-eIF2α/ATF4 pathway, supporting the findings in this work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anlotinib was developed by Nanjing Chia Tai Tianqing Pharmaceutical Co., Ltd. as a new oral molecular RTK inhibitor; it targets VEGFR1, VEGFR3, VEGFR2/KDR, PDGFR-a, c-Kit, and FGFRs 1-3 and inhibits TA and tumor cell proliferation (31,(41)(42)(43). Anlotinib may inhibit more targets than that do other RTK inhibitors, such as pazopanib, sunitinib, and sorafenib.…”
Section: Anlotinib: a Novel Inhibitor Targeting Multiple Rtksmentioning
confidence: 99%
“…Reactive oxygen species have recently emerged as important regulators of ER function and UPR activation, and ER stress and increased ROS production were detected on chemotherapy treatment in several malignancies ( Cubillos-Ruiz et al, 2017 ; Lin et al, 2019 ; Qi et al, 2020 ; Yang and et al, 2020 ). ROS are an essential component of the signaling that leads to protein misfolding and ER stress-induced cell death ( Verfaillie et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%